Effect of information awareness on attitudes toward human papillomavirus vaccination intentions in Japan - Takayuki Takahashi; Takahiro Kinoshita; Daisuke Shigemi; Yousuke Imanishi; Masahiko Sakamoto; Megumi Ichimiya; Makiko Mitsunami; Mihyon Song; Kanako Inaba (Vaccine: X)
Background: The Human Papillomavirus (HPV) vaccination rate among Japanese high school girls remains critically low, reflecting ongoing public apprehension and misinformation. This study explores the relationship between information presentation and attitudes toward HPV vaccination in Japan. Methods: We conducted a web-based survey of female high school students aged 15 to 16 and mothers of daughters of similar age across Japan. The first screening questionnaire investigated the vaccine uptake among eligible students. The detailed questions assessing awareness of HPV vaccination information, including vaccine eligibility and its cost, effectiveness, lifetime prevalence of HPV infection, and vaccine safety, were asked to the respondents. After presenting each piece of information, we investigated how the information influenced the vaccination attitudes of unvaccinated students and mothers of unvaccinated girls. Results: Data collection occurred from August 20 to August 24, 2021. Of 473 students, 68 (14.4 %) had already been vaccinated before the study. Over half of the 245 participating students were aware of vaccine eligibility and cost (68.7 %) and effectiveness (63.6 %), but fewer understood lifetime prevalence (28.7 %) and safety (45.3 %). In contrast, awareness of the same questions in 245 mothers was higher than that in the students: 90.2 %, 92.5 %, 55.4 %, and 61.1 %, respectively. Among unvaccinated students and mothers of unvaccinated girls, the intention to get vaccinated increased the most after being informed about the lifetime risks of HPV infection; 50.5 % of students and 38.8 % of mothers showed a positive attitude toward the HPV vaccination. Conclusions: Bridging the awareness gap between students and mothers is crucial for improving HPV vaccination rates. The findings underscore the potential of specific, targeted information to influence vaccination intentions, particularly regarding the HPV infection rate.